Perceived Organization Support Towards Employee Engagement and The Impact of Employee Job Satisfaction - Sulistyawati, Upik Sri; Sufriadi, Dedi (Universitas Pendidikan Ganesha, 2020)
This study was to analyze the effect of perceived organizational support on employee engagement and its impact on employee job satisfaction. This type of research is explanatory research with a quantitative approach. Hypothesis testing using the hierarchical regression analysis method with the help of SPSS version 21. The results showed that: there was a positive influence on perceived organizational support on employee engagement. with the result Z = 0.628; t = 6,096; p <0.001; there is a positive effect of perceived organizational support on employee performance indicated by the result Y = 0.791; t = 12,022; p <0.001; There is a positive influence on employee engagement on employee performance as indicated by Y = 0.323; t = 2,766; p <0.01); and employee engagement can be proven as a mediating variable on the effect of perceived organizational support on the performance of administrative employees. So, there is an effect of perceived organizational support on employee engagement and its impact on employee job satisfaction. These findings are expected to evaluate employee performance and understand the process of implementing policies for employees.